Nuptial Motifs in Composition: A Key to the Interpretation of the Song of Songs - Jasnos, Renata (Verbum vitae, 2021)
The purpose of this paper is to explore the references to nuptial customs found in the Song of Songs as well as their place in relation to the structure of the text. The first stage of analysis consists of identifying various types of these references, while the second stage involved analysing and evaluating their positioning within the composition of the Song of Songs as an expression of the editorial intent of the biblical writers. The study has used elements of form analysis and lexical analysis as well as a comparative analysis of biblical and non-biblical/sub-biblical texts. The analysis revealed that the most important places in the structure of the Song of Songs are allocated to the so-called “poetic episodes,” which have been distinguished earlier, concerning the different stages of nuptials - engagement negotiations, wedding procession, wedding feast and consummation of the marriage. Therefore, they constitute a point of reference for the interpretation of the remaining songs and at the same time the teachings of the sages in the Song of Songs.